Mitochondrial Approaches to Protect Against Cardiac Ischemia and Reperfusion Injury - Camara, Amadou K.; Bienengraeber, Martin; Stowe, David F. (Frontiers in Physiology, 2011)
The mitochondrion is a vital component in cellular energy metabolism and intracellular signaling processes. Mitochondria are involved in a myriad of complex signaling cascades regulating cell death vs. survival. Importantly, mitochondrial dysfunction and the resulting oxidative and nitrosative stress are central in the pathogenesis of numerous human maladies including cardiovascular diseases, neurodegenerative diseases, diabetes, and retinal diseases, many of which are related. This review will examine the emerging understanding of the role of mitochondria in the etiology and progression of cardiovascular diseases and will explore potential therapeutic benefits of targeting the organelle in attenuating the disease process. Indeed, recent advances in mitochondrial biology have led to selective targeting of drugs designed to modulate or manipulate mitochondrial function, to the use of light therapy directed to the mitochondrial function, and to modification of the mitochondrial genome for potential therapeutic benefit. The approach to rationally treat mitochondrial dysfunction could lead to more effective interventions in cardiovascular diseases that to date have remained elusive. The central premise of this review is that if mitochondrial abnormalities contribute to the etiology of cardiovascular diseases (e.g. ischemic heart disease), alleviating the mitochondrial dysfunction will contribute to mitigating the severity or progression of the disease. To this end, this review will provide an overview of our current understanding of mitochondria function in cardiovascular diseases as well as the potential role for targeting mitochondria with potential drugs or other interventions that lead to protection against cell injury.